Improving Global Planning Education by Centering the Experience of International Students in U.S. and Canadian Planning Schools. (September 2022) - Fan, Yingling; Hoey, Lesli; Das, Ashok; Irazábal, Clara; Stiftel, Bruce; Shatkin, Gavin; Owusu, Francis; Doan, Petra; Fang, Yiping; Rumbach, Andrew
This report examines ways to better support international students in U.S. and Canadian planning schools based on a survey and focus groups conducted by the Association of Collegiate Schools of Planning Global Planning Education Committee (GPEC). Findings show that international students often face alienation and structural barriers to navigating universities and living in an unfamiliar culture, along with identity ambiguity, inadequate career services, and narrowly focused urban planning curricula. This suggests the need for greater mentorship; explicit recognition in diversity, equity, and inclusion (DEI) efforts; tailored professional development; and more holistic support systems.